Teachers’ Beliefs About Children’s Anger and Skill in Recognizing Children’s Anger Expressions - Hagan, Courtney A.; Halberstadt, Amy G.; Cooke, Alison N.; Garner, Pamela W. (Frontiers in Psychology, 2020)
Everyday beliefs often organize and guide motivations, goals, and behaviors, and, as such, may also differentially motivate individuals to value and attend to emotion-related cues of others. In this way, the beliefs that individuals hold may affect the socioemotional skills that they develop. To test the role of emotion-related beliefs specific to anger, we examined an educational context in which beliefs could vary and have implications for individuals’ skill. Specifically, we studied 43 teachers’ beliefs about students’ anger in the school setting as well as their ability to recognize expressions of anger in children’s faces in a dynamic emotion recognition task. Results revealed that, even when controlling for teachers’ age and gender, teachers’ belief that children’s anger was useful and valuable in the school setting was associated with teachers’ accuracy at recognizing anger expressions in children’s faces. The belief that children’s anger was harmful and not conducive to learning, however, was not associated with teachers’ accuracy at recognizing children’s anger expressions. These findings suggest that certain everyday beliefs matter for predicting skill in recognizing specific emotion-related cues.